Shaping the Character of Early Childhood: Teacher Strategies for Improving Emotional Regulation in Early Childhood at Tunas Pancasila Krasakageng Kindergarten - Kurnia Mufalakhah; Ichsan Ichsan (Child Kingdom : Jurnal Pendidikan Anak Usia Dini, 2024)
This research is motivated by the problems faced by children who basically have varying emotional levels. Early childhood is faced with the demand to learn to control their own emotions from an early age. The aim of this research is to understand how emotional regulation occurs in young children in Group B1 at the Tunas Pancasila Krasakageng Kindergarten and why emotional regulation can occur in children. This research also aims to identify the strategies used by teachers to improve emotional regulation abilities in early childhood. This research uses a qualitative method with a case study type of research. This research was conducted on 23-24 November 2023 at the Tunas Pancasila Krasakageng Kindergarten in Group B1. The subjects of this research were the school principal, homeroom teacher and Group B1 children. Data collection techniques were carried out using observation, interviews and documentation methods. Data analysis was carried out by condensing data, presenting data, and drawing conclusions. Meanwhile, the data validity test used is triangulation of techniques and sources. The results of this research are that there are still children who have not implemented emotional regulation well and have not been able to control their emotions independently. The teacher's strategy for improving emotional regulation in young children in Group B1 of the Tunas Pancasila Krasakageng Kindergarten is: (1) The teacher calms the child if the child shows emotion, 2) Provides examples of how to overcome disappointment and tension in the child. (3) Provides positive rewards. in children when they are able to behave well. (4) The teacher provides a calm and comfortable atmosphere for learning activities. (5) Teaches children to play supportively. (6) Teachers establish good communication with children without discriminating, (7) Introduce students to an attitude of tolerance